Avaliação de procedimentos de preparo de amostra de amendoim in natura para análise de aflatoxinas - Calori-Domingues, Maria Antonia; Rechdan, Rafael Condino; Moretti, Ademar; Gloria, Eduardo Micotti da; Zambello, Ivani Valarini; Corrente, José Eduardo [UNESP]; Dias, Carlos Tadeu dos Santos (Sociedade Brasileira de Química, 2010)
The variability in aflatoxin B1 concentration among peanut subsamples of 4 sample preparation procedures was evaluated. For each procedure, 18 samples were prepared involving dry comminuting/homogenization or dry roughly comminuting followed by the preparation of a aqueous slurry. Ten analytical samples were withdrawn from each sample/procedure and analyzed by thin layer chromatography. The coefficient of variation (CV%) among each set of 10 analytical samples was assumed to be associated with the sample preparation procedure. The procedure that made use of a subsample mill and preparation of a subsample slurry, showed lower variability (CV%) among the analytical subsamples.
Evaluation of sample preparation procedures for aflatoxin analysis in raw peanut
Keywords: sample preparation; aflatoxin; variability